Deregulation, privatisation and marketisation of Nordic comprehensive education: social changes reflected in schooling. Issue 1 (2nd January 2018) - Dovemark, Marianne; Kosunen, Sonja; Kauko, Jaakko; Magnúsdóttir, Berglind; Hansen, Petteri; Rasmussen, Palle
ABSTRACT: The Nordic countries are often perceived as a coherent group representing the Nordic model of welfare states, with a strong emphasis on the public provision of universal welfare and a strong concern with social equality. But today we see a change in the Nordic model as part of a global knowledge economy. The aim of this article is to examine education in the five Nordic countries utilising three dimensions of political change: deregulation, marketisation and privatisation. We also analyse the parallel changes in relation to segregation and differentiation in education. The analysis shows that the themes related to deregulation seem to show fairly similar patterns and structures in all contexts. The emerging differences were discovered mainly in the themes of marketisation and privatisation. Institutional segregation emerges in all Nordic countries to different extents along the lines of these three processes, and we observe a simultaneous social segregation and differentiation with an ambiguous connection to them. Based on these findings, the question of what is left of the "Nordic model" could be raised.